KEPENTINGAN FINLANDIA TERHADAP INDONESIA DALAM KERJASAMA DIBIDANG BIOMASSA PERIODE 2014-2017 - Yulius Danu Setianto (2020)
Cooperation between Indonesia and Finland in the field of renewable energy is a collaboration that has the potential to benefit both countries. This collaboration is carried out to overcome the limited availability of fossil energy which is currently the main ingredient in producing energy. With this collaboration, it is hoped that Indonesia can meet its growing energy needs along with the development of society and industry through renewable energy. Finland is one of the countries that focus on clean and renewable energy to spearhead this collaboration. In this collaboration, the two states are brought together and combined to form a mutually beneficial cooperation both in terms of economic, social and political.